2021
DOI: 10.30901/2658-6266-2020-4-o2
|View full text |Cite
|
Sign up to set email alerts
|

SSR analysis of modern Russian potato varieties using DNA samples of nomenclatural standards

Abstract: The N.I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) is developing new approaches to documentation of national cultivars, taking into account recommendations of the International Code of Nomenclature for Cultivated Plants in parallel with methods of genetic certification. The nomenclatural standard of a particular cultivar represented by a herbarium specimen can be used as a reference for verifying authenticity and uniformity of cultivar specimens obtained from various sources. The verificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
3
0
3
Order By: Relevance
“…Salimi et al (2016) used SSRs to determine allelic diversity within and among potatoes from different geographical regions and reported numerous alleles per locus, ranging from two (STM1049) to nine (STM1104), respectively, which is consistent with the present data, where STM1049 showed three alleles and STM1104 showed eight alleles. Antonova et al (2020) investigated the genetic diversity of potatoes using the set of alleles in the 14 examined SSR loci but indicated that with an increased number of the genotyped accessions, the resolving power of only these 14 SSR markers was not sufficient because of the low values of bootstrap coefficients. Duan et al (2019) used 16 parental cultivars widely used in breeding to screen 138 SSR markers, where 20 were polymorphic that were used to analyze the genetic diversity of 217 potato cultivars grown in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salimi et al (2016) used SSRs to determine allelic diversity within and among potatoes from different geographical regions and reported numerous alleles per locus, ranging from two (STM1049) to nine (STM1104), respectively, which is consistent with the present data, where STM1049 showed three alleles and STM1104 showed eight alleles. Antonova et al (2020) investigated the genetic diversity of potatoes using the set of alleles in the 14 examined SSR loci but indicated that with an increased number of the genotyped accessions, the resolving power of only these 14 SSR markers was not sufficient because of the low values of bootstrap coefficients. Duan et al (2019) used 16 parental cultivars widely used in breeding to screen 138 SSR markers, where 20 were polymorphic that were used to analyze the genetic diversity of 217 potato cultivars grown in China.…”
Section: Discussionmentioning
confidence: 99%
“…UPGMA dendrogram indicated that American genotypes exhibit higher expected heterozygosity than European genotypes, concluding that SSRs are appropriate markers for evaluating genetic diversity within and among potatoes from different geographical regions. Antonova et al (2020) found that a variety of potatoes from different countries were combined into mixed groups, probably indicating the intensive exchange of breeding material, using the set of alleles in the 14 examined SSR loci. Due to the increased number of the genotyped accessions, the resolving power of only these 14 SSR markers was not sufficient because of the low values of bootstrap coefficients.…”
Section: Introductionmentioning
confidence: 99%
“…DNA extraction. DNA was extracted from 10-day-old seedlings using a modified CTAB extraction technique (Antonova et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…В ВИР данное направление включает дополнительные молекулярно-генетические и биотехнологические подходы, с целью создания генетических паспортов образцов сортов, переданных их авторами в Гербарий ВИР, и сохранения генотипированных клонов в живом виде в контролируемых условиях in vitro и крио коллекций . Развитие данной комплексной стратегии уже привело к созданию более 60 Биотехнология и селекция растений 2022;5(4) номенклатурных стандартов и молекулярно-генетических паспортов российских сортов картофеля Antonova et al, 2020;Klimenko et al, 2020;Fomina et al, 2020a,b;Rybakov et al, 2020). (Fomina et al, 2020a;Rybakov et al, 2020), то же относится к условиям ПЦР и контрольным образцам для проведения молекулярного скрининга и SSR-анализа (Antonova et al, 2020;Klimenko et al, 2020;Rybakov et al, 2020) (см.…”
Section: Introductionunclassified
“…Развитие данной комплексной стратегии уже привело к созданию более 60 Биотехнология и селекция растений 2022;5(4) номенклатурных стандартов и молекулярно-генетических паспортов российских сортов картофеля Antonova et al, 2020;Klimenko et al, 2020;Fomina et al, 2020a,b;Rybakov et al, 2020). (Fomina et al, 2020a;Rybakov et al, 2020), то же относится к условиям ПЦР и контрольным образцам для проведения молекулярного скрининга и SSR-анализа (Antonova et al, 2020;Klimenko et al, 2020;Rybakov et al, 2020) (см. Приложение 1/ Supplement 1).…”
Section: Introductionunclassified